2018
DOI: 10.1111/1911-3838.12171
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends within Social and Environmental Accounting Research: A Literature Review

Abstract: Given the recent rise in the evolution and maturity of social and environmental accounting (SEA) research and scholarship, we provide a literature review of the current trends within this area in a concise and harmonized manner for a wider audience in academia and practice. More specifically, we visit the current state of scholarly work, which can be useful in facilitating future research questions and further development of SEA research associated with relations between corporate social performance (CSP), cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 159 publications
6
55
0
4
Order By: Relevance
“…Historically, Canadian chemical, resource, and energy sector companies have been the first to release nonfinancial reports on their environmental impacts. This is consistent with previous studies that have found that industries with higher impact (e.g., environmental degradation) engage more extensively in corporate social responsibilty (CSR) reporting (Cho, Laine, Roberts, and Rodrigue, 2018;Cho and Patten, 2007;Chung and Cho, 2018;Young and Marais, 2012).…”
Section: Industry Trendssupporting
confidence: 92%
“…Historically, Canadian chemical, resource, and energy sector companies have been the first to release nonfinancial reports on their environmental impacts. This is consistent with previous studies that have found that industries with higher impact (e.g., environmental degradation) engage more extensively in corporate social responsibilty (CSR) reporting (Cho, Laine, Roberts, and Rodrigue, 2018;Cho and Patten, 2007;Chung and Cho, 2018;Young and Marais, 2012).…”
Section: Industry Trendssupporting
confidence: 92%
“…Consistently with this, investors are positive about firms with a high CSP [1]. As the importance of "social responsibility" is emphasized, studies have increasingly analyzed the impact of corporate social responsibility (CSR) activities from various perspectives, such as cost of equity capital, earnings quality, and financial performance [2][3][4][5][6]. They generally find lower cost of equity capital, higher financial reporting quality, and company reputation improvement, supporting the benefits of CSR.…”
Section: Introductionmentioning
confidence: 76%
“…Our findings are useful to investors by providing a possibility for EOM to be used in distinguishing ethical managers. In addition, we contribute to the expansion of the literature in CSR from an auditing perspective, which has been noted for a lack of active research, by showing the usefulness of the audit report information on CSR [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…It is also important to communicate social information to stakeholders about the social impacts of the organization that would affect the society in which it operates. (GRI, 2013;Chung & Cho, 2018). The economic and financial data serve to demonstrate the economic and financial efficiency in the management of the organization's resources (Bushman & Smith, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Expand the number of social indicators could be a disclosure policy to improve communication with stakeholders (Hackston & Milne, 1996;Moneva, et al, 2006;O'Dwyer & O'Sullivan 2009). Stakeholders expect that organizations can demonstrate that they are operating in accordance with their stated social contract (GRI, 2013;Chung & Cho, 2018). Table 5 presents 29 economic and financial matters suggested by all stakeholders.…”
Section: Disclosure Indicators Suggested By Stakeholdersmentioning
confidence: 99%